A Three-Level Framework for Assessing and Implementing Environmental Flows - Opperman, Jeffrey J.; Kendy, Eloise; Tharme, Rebecca E.; Warner, Andrew T.; Barrios, Eugenio; Richter, Brian D. (Frontiers in Environmental Science, 2018)
In the decade since the Brisbane Declaration (2007) called upon governments and other decision makers to integrate environmental flows into water management, practitioners have continued to seek ways to expand implementation of flow restoration or protection. The science and practice of environmental flow assessment have evolved accordingly, generating diverse methods of differing complexity from which water managers or regulators need to select an approach best fitting their context. Uncertainty over method choice remains one of several of the more readily overcome barriers that have contributed to slowing the implementation of environmental flows. In this paper, we introduce a three-level framework intended to help overcome such barriers by intertwining holistic environmental flow assessment with implementation. The three levels differ based on the availability of resources and level of resolution required in the flow recommendations, with the framework designed to guide the user toward implementation at any level as soon as possible, based on at least some of the recommendations. Level 1 is a desktop analysis based on existing data, typically conducted by one or a few scientists. Level 2 is similarly mostly reliant on existing information, but brings together a multidisciplinary set of experts within a facilitated workshop setting to use both this knowledge and professional judgment to develop flow recommendations and fill data gaps. The most comprehensive assessment level, Level 3, guides the collection of new data and/or construction of models to test hypotheses developed by the expert team. Key characteristics of this framework include: (1) methods are matched to the levels of resources available and certainty required; funds for research are invested strategically to address critical knowledge gaps and thereby reduce uncertainty; (2) the framework is iterative and information generated at one level provides the foundation for, and identifies the need for, higher levels and; and (3) processes for flow assessment and implementation are intertwined, meaning they move forward in coordinated fashion, with each process informing the other. Using practical cases from North America, we illustrate how environmental flow assessment at each level has led to implementation, with changes in policy or management.